TINGKAT KEDISIPLINAN MENAATI TATA TERTIB - Shinta Muliawati; Dini Rakhmawati; srimulyaningsih (Universitas Muhammadiyah Metro, 2024)
The purpose of this study was to ascertain the degree of discipline among class XI students at SMA Negeri 14 Semarang with regard to following the rules and regulations. This study used the scale method in a quantitative manner. In order to choose 268 class XI pupils, the sampling approach in this study used probability sampling, which is based on simple random sampling. Studies on the degree of discipline among class XI students at SMA Negeri 14 Semarang in adhering to the laws and regulations With 120 pupils, the highest percentage level is 44.8%, the very high category is 7.5% with 20 students, high category 32.5% totaling 87, and low category 41 students with a percentage of 15.3%.